THE FEATURES OF MARKETING STRATEGY IN THE OIL AND GAS INDUSTRY - Zh. Basshieva (Academic Journal of Physical and Chemical Sciences, 2019)
The development of oil companies depends on their ability to predict and respond flexibly to the changing conditions of the external environment, to gain competitive advantages in the struggle in the markets. In such conditions, the role of strategic management in oil companies increases, which determines the relevance of the article, which reveals the directions and methods of formation and implementation of the marketing strategy for the development of oil complex enterprises. The article discusses the trends in the oil and gas market and their impact on the marketing strategies of oil companies in the near future. The article also substantiates the importance of marketing to coordinate the activities of participants in technological processes within the oil and gas industry, improve the efficiency of enterprises, achieve competitive advantages, as well as to reduce risks in management decisions.